FISH " SEED" RESOURCES OF SOME RIVERS IN SOUTH INDIA - David, A; Govind, B V; Rao, N G S; Rajagopal, K V (Indian Journal of Fisheries, 2011)
Information on the quality and magnitude of fish "seed" resources ofpeninsular Indian rivers is fragmentary. Riverine collection of major carp spawncontinues to remain the primary source of spawn production in the country,accounting for 91.6% of the total spawn production (Govt, of India—Report, 1966).Qualitative and quantitative aspects of spawn occurrence in the Godavari andKrishna rivers have been analysed by Chacko (1946), Chacko and Sreenivasan(1955) and Ibrahim (1961). Raj (1930) reported the breeding of Catla (implantedinto the Cauvery from the Godavari since 1922) at Hoginakal falls above MetturReservoir. Ganapathi and Alikunhi (1949) reported collection of spawn andhatchlings of major carps in large numbers from the Godavari, Tungabhadra,Cauvery, Bhavani and Moyar rivers. David (1959) indicated the known spawninggrounds and fry and fingerling collection sites of indigenous carps of peninsularIndian rivers.